Psychological Impacts among Older and Younger People Living with HIV/AIDS in Nanning, China - Hongjie Liu; Xin He; Judith A. Levy; Yongfang Xu; Chunpeng Zang; Xinqin Lin (Journal of Aging Research)
Objectives. The HIV epidemic has drastically increased among older adults in China, yet little research has examined the psychological impacts among older and younger people living with HIV/AIDS (PLWHAs). This study examined and compared self-efficacy, depression, well-being, and quality of life among older and younger PLWHAs in China. Method. A two-stage sampling procedure was used to recruit a final sample of 148 participants. Older adults were defined as age 50 and older. Result. Compared to younger PLWHAs aged 18–49 years old, older PLWHAs reported lower levels of well-being (7.6 versus 11.4), higher levels of depression (18.6 versus 15.8), and poorer quality of life. Self-efficacy was similar among older (23.9) and younger (24.6) PLWHAs. A higher level of depression among older PLWHAs was associated with much lower levels of subjective well-being and quality of life (physical health and psychological health). Conclusion. The findings suggest that older PLWHAs face psychological problems and mental health challenges beyond those experienced by younger PLWHAs. Intervention programs dedicated to improving mental health and quality of life are greatly needed for HIV infected older adults.